Delays from neoadjuvant chemotherapy to interval debulking surgery and survival in ovarian cancer. Issue 10 (9th October 2020) - Liu, Ying L; Zhou, Qin C; Iasonos, Alexia; Filippova, Olga T; Chi, Dennis S; Zivanovic, Oliver; Sonoda, Yukio; Gardner, Ginger; Broach, Vance; OCearbhaill, Roisin; Konner, Jason A; Aghajanian, Carol A; et al.
Abstract : Introduction: Delays from primary surgery to chemotherapy are associated with worse survival in ovarian cancer, however the impact of delays from neoadjuvant chemotherapy to interval debulking surgery is unknown. We sought to evaluate the association of delays from neoadjuvant chemotherapy to interval debulking with survival. Methods: Patients with a diagnosis of stage III/IV ovarian cancer receiving neoadjuvant chemotherapy from July 2015 to December 2017 were included in our analysis. Delays from neoadjuvant chemotherapy to interval debulking were defined as time from last preoperative carboplatin to interval debulking >6 weeks. Fisher's exact/Wilcoxon rank sum tests were used to compare clinical characteristics. The Kaplan–Meier method, log-rank test, and multivariate Cox Proportional-Hazards models were used to estimate progression-free and overall survival and examine differences by delay groups, adjusting for covariates. Results: Of the 224 women, 159 (71%) underwent interval debulking and 34 (21%) of these experienced delays from neoadjuvant chemotherapy to interval debulking. These women were older (median 68 vs 65 years, P=0.05) and received more preoperative chemotherapy cycles (median 6 vs 4, P=0.003). Delays from neoadjuvant chemotherapy to interval debulking were associated with worse overall survival (HR 2.4 95% CI 1.2 to 4.8, P=0.01), however survival was not significantly shortened after adjusting for age, stage, and complete gross resection, HR 1.66 95% CI 0.8 to 3.4, P=0.17. Delays from neoadjuvant chemotherapy to interval debulking were not associated with worse progression-free survival (HR 1.55 95% CI 0.97 to 2.5, P=0.062). Increase in number of preoperative cycles (P=0.005) and lack of complete gross resection (P<0.001) were the only variables predictive of worse progression-free survival. Discussion: Delays from neoadjuvant chemotherapy to interval debulking were not associated with worse overall survival after adjustment for age, stage, and complete gross resection.